The Role of Parental Communication in Improving Early Childhood Language Intelligence Through Learning the Qur'an and Hadith - Monica Chandra; Mursal Aziz; Dedi Sahputra Napitupulu (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This investigate employments a subjective approach to look at the part of parental communication in upgrading children's dialect insights through the Qur'an and Hadith in PIAUD Labura . Parents play a crucial role in shaping this intelligence, so effective strategies are needed to overcome challenges. One of the key steps is to improve religious understanding by attending Quranic study classes, participating in religious discussions, or reading Islamic books. Establishing a consistent learning routine at home is also essential, such as setting aside time each day to read, memorize, and discuss the Qur'an and Hadith with children. Additionally, creative methods like storytelling about the prophets or using Islamic educational apps can make learning more engaging and enjoyable for children. Good communication between parents and teachers is important to ensure continuity between home and school education. Parents should also actively participate in school meetings and events to support their child’s development more effectively. Moreover, encouraging children to ask questions, engage in discussions, and build a warm emotional connection with them strengthens their involvement in the learning process. Educational technology can be used as a tool to support this learning, and forming small study groups with peers can further encourage interaction and discussion. These strategies enable parents to overcome obstacles and maximize their role in enhancing children's language intelligence through the Qur'an and Hadith.